1996
DOI: 10.1093/hmg/5.10.1533
|View full text |Cite
|
Sign up to set email alerts
|

Treacher Collins syndrome may result from insertions, deletions or splicing mutations, which introduce a termination codon into the gene

Abstract: Treacher Collins syndrome is an autosomal dominant disorder of craniofacial development the features of which include conductive hearing loss and cleft palate. Recently, the Treacher Collins syndrome gene (TCOF1) has been positionally cloned and a series of five mutations within the coding sequence of the gene identified. In the current investigation, seven exons of TCOF1 have been identified which has permitted the identification of additional mutations in the gene. The mutations that have been identified are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
42
0
9

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 24 publications
2
42
0
9
Order By: Relevance
“…Although RNA and parental samples were not available to test this hypothesis a similar mechanism was proposed for another variant, c.2196G4A, that was confirmed by RT-PCR analysis. 23 Two other novel variants identified were considered less likely to be pathogenic, but could not be ruled out entirely as no other obviously pathogenic change could be identified. In the first case, patient 195 presented with microtia, atresia of the external ear canal, mild mandibular hypoplasia and a bifid uvula and was found to have c.2762C4T (p.(Pro921Leu)) in exon 16 of TCOF1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although RNA and parental samples were not available to test this hypothesis a similar mechanism was proposed for another variant, c.2196G4A, that was confirmed by RT-PCR analysis. 23 Two other novel variants identified were considered less likely to be pathogenic, but could not be ruled out entirely as no other obviously pathogenic change could be identified. In the first case, patient 195 presented with microtia, atresia of the external ear canal, mild mandibular hypoplasia and a bifid uvula and was found to have c.2762C4T (p.(Pro921Leu)) in exon 16 of TCOF1.…”
Section: Discussionmentioning
confidence: 99%
“…In the other two cases the deletion extended into the 3¢-UTR, and may therefore extend into downstream genes. Patient 8 presented with dysmorphic features consistent with a diagnosis of TCS, and was shown to have a deletion of exons [23][24][25][26], that removes the C-terminal region of treacle important for localisation to the nucleolus. Array CGH analysis suggested that the deletion did not extend into the downstream CD74 gene.…”
Section: Discussionmentioning
confidence: 99%
“…Most mutations identified in the TCOF1 gene are deletions resulting in a truncated protein (Gladwin et al 1996;Splendore et al 2000;Marszalek et al 2003). No genotype/phenotype correlations have been found.…”
Section: Introductionmentioning
confidence: 99%
“…Das 35 mutações patogênicas descritas até o momento, apenas uma resulta da troca de aminoácidos (missense), enquanto todas as outras vão levar à produção de uma proteína truncada. A maior parte dessas mutações é composta por deleções, mas inserções, alterações na emenda do RNAm (splicing) e mutações sem sentido (nonsense) também já foram descritas (The Treacher Collins Syndrome Collaborative Group, 1996;Gladwin et al, 1996;Wise et al, 1997;Edwards et al, 1997). Com base nessas observações, o mecanismo molecular proposto para a síndrome foi a haploinsuficiência.…”
Section: Introductionunclassified
“…
Group, 1996;Gladwin et al, 1996;Wise et al, 1997;Edwards et al, 1997Proporção entre casos isolados e familiais: Quinze dentre os 26 propósitos com mutações identificadas no gene TCOF1 foram encaminhados como casos isolados. Entre esses, nos 10 casos onde possuíamos DNA disponível do pai e da mãe, a paternidade foi confirmada através da análise de marcadores polimórficos.
…”
unclassified